PREDICTION OF EROSION EFFECT DUE TO CAVITATION ON AL-MOSUL POWER PLANT TURBINE (Journal of Engineering, 2008)
In the field of hydraulic power plant, the cavitation is responsible of sever erosion which requires periodic unit shutdowns for inspection and repairs. Al-Mosul hydroelectric power plant is chosen as model in this study. Computer programs are developed by using the velocity gradient method to analyze the flow in the runner blades of the turbine (Francis Turbine) to calculate the available cavitation and compared with the critical cavitation. The erosion of the runner material (erosion rate, weight of lost material and mean depth of erosion) is also calculated to limit the operation hours of the power plant. The presented work shows that the cavitation appears on the underside of the turbine (Francis Turbine) blades in the trailing edge at distance of 82% from the leading edge due to decrease in pressure, flow separation and interference zone. This causes erosion depth of about 4 mm for the first four years of operation which represents about 17% of the blade thickness of the trailing edge. It is found that the operation hours of Al-Mosul power plant should not exceed 24000 operation hour. A good agreement is found between the prototype data obtained from the computer program analysis and experimental visualization shown in the literature and theoretical solution.